2020
DOI: 10.3390/min10090797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Co-Crystallising Sulphides and Precipitation Mechanisms on Sphalerite Geochemistry: A Case Study from the Hilton Zn-Pb (Ag) Deposit, Australia

Abstract: High-tech metals including Ge, Ga and In are often sourced as by-products from a range of ore minerals, including sphalerite from Zn-Pb deposits. The Hilton Zn-Pb (Ag) deposit in the Mount Isa Inlier, Queensland, contains six textural varieties of sphalerite that have formed through a diverse range of processes with variable co-crystallising sulphides. This textural complexity provides a unique opportunity to examine the effects of co-crystallising sulphides and chemical remobilisation on the trace element geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Overlap in sphalerite compositions may indicate complex host rock lithologies of the deposits as compared to the broad lithological classification used in our PCA. For example, the Hilton deposit in Australia is dominantly hosted in carbonaceous shale, however the host rock also comprises of dolomites (Cave, Lilly, & Hong, 2020b). On the other hand, sphalerite from quartz–mica‐feldspar gneiss and metapelitic gneiss do not show any distinct clusters in PC1‐PC2 score plot (Figure 9k), which can be attributed to insufficient data of sphalerite from these lithologies (Appendix B).…”
Section: Discussionmentioning
confidence: 99%
“…Overlap in sphalerite compositions may indicate complex host rock lithologies of the deposits as compared to the broad lithological classification used in our PCA. For example, the Hilton deposit in Australia is dominantly hosted in carbonaceous shale, however the host rock also comprises of dolomites (Cave, Lilly, & Hong, 2020b). On the other hand, sphalerite from quartz–mica‐feldspar gneiss and metapelitic gneiss do not show any distinct clusters in PC1‐PC2 score plot (Figure 9k), which can be attributed to insufficient data of sphalerite from these lithologies (Appendix B).…”
Section: Discussionmentioning
confidence: 99%
“…Blocks of two standards (one NIST 610 and one GSE-2G) and one MASS-1 sulfide standard analyses were followed by five to eight unknown samples. For sphalerite, the following 18 isotopes were measured (with their respective dwell times in milliseconds listed in parentheses): 34 S, 55 Mn, 57 Fe, 59 Co, 60 Ni, 65 Cu, 66 Zn, 71 Ga, 74 Ge, 75 As, 77 Se, 107 Ag, 111 Cd, 118 Sn, 121 Sb, 126 Hg, 205 Tl, and 208 Pb, corresponding to a total dwell time of 180 ms. The MASS-1 sulfide standard [37] was used as the primary standard for calibrating 34 S, 55 Mn, 57 Fe, 59 Co, 60 Ni, 65 Cu, 66 Zn, 71 Ga, 74 Ge, 75 As, 77 Se, 107 Ag, 111 Cd, 118 Sn, 121 Sb, 126 Hg, 205 Tl, and 208 Pb.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…The main ore stage sulfide minerals in the George Fisher, Hilton, and Mount Isa massive sulfide deposits are pyrite, sphalerite, galena, chalcopyrite, and pyrrhotite (e.g., Valenta, 1994;Chapman, 2004;Cave et al, 2020a;Cave et al, 2020b). At the George Fisher deposit it is generally accepted that sulfide mineralization formed epigenetically and during multiple stages (Chapman 1999;Murphy, 2004;Rieger et al, 2020a), although the volumetric importance of individual ore stages (syn-diagenetic vs. syn-deformation) and the relationship of Zn-Pb and Cu-Zn-Pb mineralization are not clear.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Indeed, it has been suggested that Mount Isa Cu was sourced from mafic volcanic rocks in the sequences below the deposits (Eastern Creek Volcanics; e.g., Heinrich et al, 1989;Hannan et al, 1993). Sphalerite and chalcopyrite associated with Cu-mineralization at Mount Isa and Hilton is also relatively enriched in Co (Cave et al, 2020a;Cave et al, 2020b), which may indicate that fractionation effects of Co among pyrite and other sulfide phases were relatively minor and that Cu-mineralization at George Fisher formed from relatively Co-rich fluids coeval with Mount Isa and Hilton Cu.…”
Section: Ore Stagementioning
confidence: 99%